Constraining the IMF at Pluto Using New Horizons SWAP Data and Hybrid Simulations. Issue 3 (9th March 2019) - Barnes, N. P.; Delamere, P. A.; Strobel, D. F.; Bagenal, F.; McComas, D. J.; Elliott, H. A.; Valek, P.; Weaver, H. A.; Ennico, K.; Young, L. A.; Stern, S. A.
Abstract: New Horizons did not carry a magnetometer, so there is no direct way to know the strength of the Interplanetary Magnetic Field (IMF) at the time of the flyby. Using a hybrid model together with a detailed model of the Solar Wind Around Pluto (SWAP) instrument (McComas et al., 2007, https://doi.org/10.1007/s11214-007-9205-3 ) we have identified three observables that are sensitive to IMF strength: the width of Pluto's heavy ion tail, the energy of heavy ions, and the profile of thermal pressure along the New Horizons trajectory. By comparing simulation to data we infer that the IMF strength was most likely near or below ∼0.1 nT. We also show that the shell distribution of Interstellar Pickup Ions is important for reproducing these observations due to its effect on global pressure balance. Key Points: Numerical experiments suggest that an IMF strength near or below 0.1 nT is consistent with New Horizons data High plasma beta in the wake adequately explains the broad heavy ion tail that was observed The shell distribution of interplanetary pickup ions is important for understanding Pluto's plasma wake